A comparative assessment of adipose‐derived stem cells from subcutaneous and visceral fat as a potential cell source for knee osteoarthritis treatment. Issue 9 (4th April 2017) - Tang, Yan; Pan, Zhang‐yi; Zou, Ying; He, Yi; Yang, Peng‐yuan; Tang, Qi‐qun; Yin, Feng
Abstract: The intra‐articular injection of adipose‐derived stem cells (ASCs) is a novel potential therapy for patients with osteoarthritis (OA). However, the efficacy of ASCs from different regions of the body remains unknown. This study investigated whether ASCs from subcutaneous or visceral adipose tissue provide the same improvement of OA. Mouse and human subcutaneous and visceral adipose tissue were excised for ASC isolation. Morphology, proliferation, surface markers and adipocyte differentiation of subcutaneous ASCs (S‐ASCs) and visceral ASCs (V‐ASCs) were analysed. A surgically induced rat model of OA was established, and 4 weeks after the operation, S‐ASCs, V‐ASCs or phosphate‐buffered saline (PBS, control) were injected into the articular cavity. Histology, immunohistochemistry and gene expression analyses were performed 6 weeks after ASC injection. The ability of ASCs to differentiate into chondrocytes was assessed by in vitro chondrogenesis, and the immunosuppressive activity of ASCs was evaluated by co‐culturing with macrophages. The proliferation of V‐ASCs was significantly greater than that of S‐ASCs, but S‐ASCs had the greater adipogenic capacity than V‐ASCs. In addition, the infracted cartilage treated with S‐ASCs showed significantly greater improvement than cartilage treated with PBS or V‐ASCs. Moreover, S‐ASCs showed better chondrogenic potential and immunosuppression in vitro . Subcutaneous adipose tissue is an effective cell source for cell therapy of OA as it promotes stem cell differentiation into chondrocytes and inhibits immunological reactions.